1/(√2+1)
Multiply by (√2-1)/(√2-1):
(√2-1)/((√2+1)(√2-1))
Expand:
(√2-1)/(2+√2-√2-1)
Simplify:
(√2-1)/(1)
√2-1
2006-11-10 11:58:23
·
answer #1
·
answered by Pascal 7
·
0⤊
0⤋
i don't know if you mean a) 1 / (squareroot of 2 plus 1) or
b) (1/squareroot of 2) + 1.
anyway, in the first case:
1/(sqrt2 + 1) ===> you multiply the numerator and denominator by its conjugate: (sqrt2 - 1).
thus:
1 times (sqrt2 - 1) ===> sqrt2 -1 over
(sqrt2 +1) times (sqrt2 -1) ===> 2 - 1 or simply 1
recall: (x+y)(x-y) = x^2 - y^2
thus, the answer is sqrt2 - 1.
for case b:
(1/sqrt2) + 1 this is easier.
first, combine the fraction and 1 with sqrt2 as the common denominator.
(1/sqrt2) + 1 ===> 1 + sqrt2 over sqrt2 or (1+sqrt2)/sqrt2
to rationalize, multiply the numerator and denominator by sqrt2:
(1+sqrt2)(sqrt2) over 2.
or:
(sqrt2 + 1)/2
note: the secret of the first solution is the multiplication of its conjugate.
2006-11-10 20:12:28
·
answer #2
·
answered by naglibog 2
·
0⤊
0⤋
Rationalise 1/(sqrt(2)+1) I assume
Note sqrt(2) x sqrt(2) = 2 Obviously and
(x - y)(x + y) = x^2 - y^2
a x b/b = a x 1 = a
Thusly
1/(sqrt(2)+1) x (sqrt(2)-1)/(sqrt(2)-1)
=(sqrt(2)-1)/(2 -1)
=sqrt(2) - 1
Follow the steps. Easy peasy.
Onya
2006-11-10 20:02:26
·
answer #3
·
answered by A S 4
·
0⤊
0⤋
for rationalising you multiply the denominator by the conjugate,in this case rt2-1 and in order that you don't change the value of the expression you multiply the numerator also by rt2-1
(rt2+1)(rt2-1)=[(rt2)^2-(1)^2] =2-1=1
[using the identity (a+b)(a-b)=(a^2-b^2).]
so the answer=(rt2-1)
2006-11-10 20:06:06
·
answer #4
·
answered by raj 7
·
0⤊
0⤋
1/(sqrt(2) +1)
multiply by (sqrt(2) - 1)/(sqrt(2) -1) which is supposed to be 1
(sqrt(2) -1)/ ((sqrt(2) + 1)(sqrt(2) -1))
= sqrt(2) - 1
idea is that (a+1)(a-1) = (a^2 -1)
so if a is sqrt(2), a^2 = 1 so a^2 - 1 = 1
2006-11-10 20:05:19
·
answer #5
·
answered by paladin 1
·
0⤊
0⤋
1/ (sq rt(2) + 1)
multiply this by (sq rt(2) - 1) / (sq rt(2) - 1)
this should get rid of the radical symbol in the denominator
work it out:
(sq rt(2) - 1) / (2 - 1)
Answer:
(sq rt(2) - 1)
2006-11-10 20:02:15
·
answer #6
·
answered by trackstarr59 3
·
0⤊
0⤋